The relationship between spiritual intelligence with self-efficacy in adolescents suffering type 1 diabetes - Mojdeh Rahmanian; Mohsen Hojat; Mojtaba Zeini Jahromi; Abdolahad Nabiolahi (Wolters Kluwer Medknow Publications, 2018)
INTRODUCTION: An important construct to consider within diabetes management and the changing landscape of diabetes therapies is self-efficacy. Self-efficacy research holds the potential to inform and assist the diabetes team as well as patients with type 1 diabetes. METHODS: In this descriptive-correlation study, 200 adolescents with type 1 diabetes were enrolled. To measure spiritual intelligence, the 24-question Spiritual Intelligence Self-Report Inventory questionnaire and to measure self-efficacy of diabetes, the Self-efficacy Questionnaire (8 questions) were used. Data collection was conducted by simple sampling. Data were analyzed using Pearson analysis, mean, and standard deviation analysis tests. RESULTS: Nearly 66% of the participants were female, the mean age of the samples was 17.10 ± 1.85 years, the mean duration of diabetes was 5.98 ± 3.79 years, and 62.5% had a history of diabetes in first-degree relatives. Almost 42% of the participants were the first children of the family and 29.5% were studying at the university.The mean score of spiritual intelligence was 60.42 ± 12.9. The mean self-efficacy score was 5.41 ± 1.87.The mean scores in the critical thinking, personal meaning production, transcendental awareness, conscious state expansion were 18.31 ± 4.33, 13.17 ± 3.36, 11.26 ± 3.36, 46.14 ± 1.04, 11.33 ± 1.04, and 11.89 ± 3.9, respectively. Cronbach's alpha level on the level of spiritual intelligence and self-efficacy was 0.903 and 0.082, respectively, at 95% confidence level. There was a significant relationship between spiritual intelligence and self-efficacy (P = 0.026). There was no significant relationship between self-efficacy with spiritual intelligence subscales. CONCLUSION: This study showed that spiritual intelligence correlates with self-efficacy and has a decisive role in improving the health of adolescents with diabetes.